Hepatitis B, Hepatitis C and Liver Disease: A Review for the Dental Practitioner. (2nd January 2022) - Macpherson, Iain; Brennan, Paul N; Dillon, John F
Abstract : The prevalence of chronic liver disease continues to rise, and important causes include viral infections, such as hepatitis B and hepatitis C. Both of these viruses can be contracted by healthcare workers through an inoculation injury and can lead to liver cirrhosis and cancer. In addition, chronic liver disease can result in disorders of liver function, including coagulopathy and abnormal metabolism of drugs widely used in dentistry. This article reviews current prevalence, transmission rates and treatment of hepatitis B and hepatitis C, as well as particular considerations for dental patients with liver disease. CPD/Clinical Relevance: Viral hepatitis remains a risk to all healthcare workers, and patients with liver disease provide various challenges when providing dental treatment.